Sustainable UNiversity Life (SUN) study: protocol for a prospective cohort study of modifiable risk and prognostic factors for mental health problems and musculoskeletal pain among university students. Issue 4 (4th April 2022) - Edlund, Klara; Sundberg, Tobias; Johansson, Fred; Onell, Clara; Rudman, Ann; Holm, Lena W; Grotle, Margreth; Jensen, Irene; Côté, Pierre; Skillgate, Eva
Abstract : Introduction: Mental health problems and musculoskeletal pain are common health problems among young adults including students. Little is known about the aetiology and prognosis of these problems in university students. We aim to determine the role of personal, sociodemographic, academic and environmental factors for risk and prognosis of symptoms of depression, anxiety and stress as well as musculoskeletal pain in university students. The constructs that will be studied are based on the biopsychosocial model and psychopathology associated with disabling pain. This model acknowledges illness to consist of interrelated mechanisms categorised into biological, psychological, environmental and social cues. Methods and analysis: This cohort study aims to recruit around 5000 Swedish full-time students. Data will be collected using five online surveys during one academic year. A subgroup (n=1851) of the cohort, recruited before the COVID-19 pandemic, receive weekly text messages with three short questions assessing mood, worry and pain, sent through the web-based platform SMS-track . Statistical analyses will include Kaplan-Meier estimates, Cox regression analyses, multinomial logistic regression analyses and generalised estimating equations. We will assess effect measure modification when relevant and conduct sensitivity analyses to assess the impact of lost to follow-up. Protocol amendments: Due to opportunity and timing of the study, with relevance to the outbreak of the COVID-19 pandemic, this study further aims to address mental health problems, musculoskeletal pain and lifestyle in university students before and during the pandemic. Ethics and dissemination: The Sustainable UNiversity Life study was approved by the Swedish ethics authority (2019-03276; 2020-01449). Results will be disseminated through peer-reviewed research papers, reports, research conferences, student theses and stakeholder communications. Trial registration number: NCT04465435 .